Product integration with applications to differential equations - Dollard, John D. (Cambridge University Press, 1984)
Originally published in 1979, this book shows the beautiful simplifications that can be brought to the theory of differential equations by treating such equations from the product integral viewpoint. The first chapter of the book, dealing with linear ordinary differential equations, should be accessible to anyone with a knowledge of matrix theory and elementary calculus. Later chapters assume more sophistication on the part of the reader. The essential unity of these subjects is illustrated by the fact that the idea of the product integral can be naturally and effectively used to deal with all of them
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Differential equations; Differential equations, Partial; Integral equations; Integralgleichung; Partielle Integration; Differentialgleichung